Embolic Strokes of Unknown Source and Cryptogenic Stroke: Implications in Clinical Practice - Nouh, Amre; Hussain, Mohammed; Mehta, Tapan; Yaghi, Shadi (Frontiers in Neurology, 2016)
Up to a third of strokes are rendered cryptogenic or of undetermined etiology. This number is specifically higher in younger patients. At times, inadequate diagnostic workups, multiple cause or an under-recognized etiology contributes to this statistic. Embolic stroke of undetermined source, a new clinical entity particularly refers to patients with embolic stroke for whom the etiology of embolism remains unidentified despite through investigations ruling out established cardiac and vascular sources. In this article, we review current classification and discuss important clinical considerations in these patients; highlighting cardiac arrhythmias and structural abnormalities, patent foramen ovale, paradoxical sources, and potentially under-recognized, vascular, inflammatory, autoimmune and hematologic sources in relation to clinical practice.